Is Gaze Cuing More Like Endogenous or Exogenous Orienting? - Murray, Nicholas E.; Drake, Richard S.; Klein, Raymond M. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2023)
People shift their attention in the direction of another person's gaze.This phenomenon, called gaze cuing, shares properties with purely endogenous (i.e., "deliberate") and purely exogenous (i.e., "reflexive") control of spatial attention. For example, as with purely endogenous orienting, gaze cues appear at visual fixation; yet, as with purely exogenous orienting, gaze cues elicit shifts of attention rapidly after their appearance. Prior experiments have shown that when controlled endogenously versus exogenously, the effects of attention upon the processing of targets are dramatically different. Briand and Klein (1987; see also Briand, 1998) showed that endogenous orienting is additive with opportunities for illusory conjunctions, whereas exogenous orienting is interactive. Klein (1994) showed that endogenous orienting is interactive with nonspatial expectancies,whereas exogenous orienting is additive. In the present project, we applied this double-dissociation strategy to attention controlled by gaze cues. In Experiment 1, gaze cuing effects (in accuracy) were additive with opportunities for illusory conjunctions (akin to endogenous control), whereas in Experiment 2, gaze cuing was additive with the nonspatial expectancy effect (akin to exogenous orienting). Therefore, in the nature of its effects upon performance, gaze cuing functions like a hybrid of endogenous and exogenous orienting.